Development of student’s work sheet based on contextual approach of the sequence and series material - Ita Desnatalia; I Made Arnawa; Irwan Irwan (International Conferences on Educational, Social Sciences and Technology)
Using Mathematics Student Worksheet (LKS) which is made by teachers before hasn’t been effective to help students in learning process. Therefore, the mathematics LKS needs to be developed to help students to find the concept themselves. Sequence and series material is important in mathematics at Vocational High School (SMK), and yet students still find difficulty to understand it. The aim of this development is to produce mathematics LKS based on contextual approach which is valid, practical and effective. This development research uses a formative evaluation model by Tjeerd Plomp. The subject of the research is the second year students of SMKN 6 Padang. Validation is done by experts / lecturers. The practicality of LKS is seen from the observation of the implementation of learning, practicality questionnaires, and interviews conducted with students and teachers. Effectiveness is seen from the results of activities and student learning outcomes.